Evaluation of hydrometeor frequency of occurrence in a limited‐area numerical weather prediction system using near real‐time CloudSat–CALIPSO observations. (21st February 2014) - Protat, A.; Young, S. A.; Rikus, L.; Whimpey, M.
<x xml:space="preserve">Abstract</x> Near real‐time measurements from the CloudSat and Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) mission are used to evaluate the representation of the hydrometeor frequency of occurrence (HFO) in the limited‐area version of the Australian Community Climate and Earth‐System Simulator (ACCESS‐A), using 1 year of collocated satellite data and model forecasts. The ACCESS‐A is found to overpredict the HFO below 12 km height (primarily over the Southern Ocean), and largely underpredict the HFO above 12 km height (primarily in the Tropics). The seasonal variability of these biases was found to be small suggesting that these model problems can be investigated with short‐term simulations. This implies that faster model improvement should be achievable using the technique proposed in this study. Selected skill scores were then analysed as a function of lead time, hydrometeor height in the troposphere and season. The highest forecast skill was found in the subtropics, mostly owing to a low incidence of false positives. Overall the ACCESS‐A forecast skill at the Southern Hemisphere mid‐latitudes is comparable to that of the North Atlantic/European version of the UK Met Office Unified Model at Northern Hemisphere mid‐latitudes. It is also found that mid‐latitude low‐level hydrometeors and tropical low‐level and high‐level hydrometeors during the Southern Hemisphere summer are the most challenging hydrometeors to simulate in the domain.